Critical Path Analysis of an Automotive Engine Laboratory Construction Project - Muhammad Alfian Hafidzin; Asep Hermawan; Yayan Heru Haerudin (Global Writing Academica Researching and Publishing, 2026)
Construction schedules presented only as bar charts provide limited information on logical dependencies, time flexibility, and the activities that govern project completion. This study evaluates the schedule of an automotive engine laboratory construction project using the Critical Path Method (CPM). Case data were consolidated from schedule documents, field observations, interviews, and project documentation into eleven work activities and one completion milestone. An Activity-on-Node network was developed and evaluated through forward-pass, backward-pass, and total-float calculations. The CPM model produced a 17-week project duration, equal to the company's original target, while revealing two critical paths: A-B-C-D-I-J-L and A-B-C-D-I-K-L. Steel erection and roofing each had two weeks of total float, whereas wall work and painting each had one week. Seven of the eleven executable activities were critical, and the two critical paths shared a 13-week common sequence. These findings demonstrate that CPM contributes not only through schedule compression but also by exposing schedule logic, focusing managerial attention, and identifying near-critical work that can become critical after a small deviation. The model is deterministic and does not incorporate resource constraints; therefore, subsequent schedule development should integrate resource leveling and probabilistic risk analysis.